Labor Mobility and the Industrial Wage Structure in the Postwar United States - Ulman, Lloyd (Quarterly Journal of Economics, 1965)
Introduction, 73. — I. Some inferences from empirical work, 74. — II. Postwar movements of wages and employment in the industrial sector, 77; changes in wages and in employment — correlations, 78; wage levels and employment changes, 79; wage levels and wage changes; wage dispersion, 80; wage rates and quit rates; related evidence, 81. — III. Some instances of major change, 85; changes in production-worker wages and employment in the period including World War II, 86; changes in wages and changes in employment — extreme values, 87; changes in compensation and employment in broad industrial categories, 1948–60, 88. — IV. Summary and policy inferences, 95.